Nova Scotia’s contribution to the development of Canadian literary canon (Philology, 2019)
The article deals with the development of Canadian literature from the perspective of the second smallest province in Canada, Nova Scotia, and its active participation in the creation of the literary canon, a subject that has plagued Canada for so long. The focus will fall on the role of Nova Scotia as one of the forefathers of Confederation, as well as its importance for the initial development and subsequent spread of literature in Canada. What is more, the article will also tackle the important notion of identity as central to both Nova Scotia and Canada on the whole, and will also be considered as an inseverable element for the economic, geographic, demographic, and literary conditions of the province and Canada.
Keywords: Canadian literary canon; Nova Scotia; regionalism; identity